2017
DOI: 10.1016/j.domaniend.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet and arginine supplementation on pancreatic mass, digestive enzyme activity, and insulin-containing cell cluster morphology during the estrous cycle in sheep

Abstract: To determine the effect of feed intake and arginine treatment during different stages of the estrous cycle on pancreatic mass, digestive enzyme activity, and histological measurements, ewes (n = 120) were randomly allocated to 1 of 3 dietary groups; control (CON; 2.14-Mcal metabolizable energy/kg), underfed (UF; 0.6 × CON), or overfed (OF; 2 × CON) over 2 yr. Estrus was synchronized using a controlled internal drug release device for 14 d. At controlled internal drug release withdrawal, ewes from each dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…In muscle tissue, insulin normally increases the energy consumption by increasing AA uptake and protein synthesis and reducing proteolysis (Hocquette et al, 1998;Richardson et al, 2004). Keomanivong et al (2017) has reported increased serum insulin in overfed ewes compared with underfed and control ewes, whereas no difference was observed in pancreatic insulin-containing cell clusters. Because of the pancreatic exhaustion due to continuous stimulation to produce excess insulin and its effects on target tissues for anabolic responses, insulin resistance may be considered one of the major contributing factors to the decreased feed efficiency associated with late finishing stages.…”
Section: Effect Of Days On Feedmentioning
confidence: 99%
“…In muscle tissue, insulin normally increases the energy consumption by increasing AA uptake and protein synthesis and reducing proteolysis (Hocquette et al, 1998;Richardson et al, 2004). Keomanivong et al (2017) has reported increased serum insulin in overfed ewes compared with underfed and control ewes, whereas no difference was observed in pancreatic insulin-containing cell clusters. Because of the pancreatic exhaustion due to continuous stimulation to produce excess insulin and its effects on target tissues for anabolic responses, insulin resistance may be considered one of the major contributing factors to the decreased feed efficiency associated with late finishing stages.…”
Section: Effect Of Days On Feedmentioning
confidence: 99%
“…Responses in pancreatic α-amylase activity to individual amino acids have varied with the type of amino acid, length of infusion, and animal species. Arginine administration through jugular blood did not influence pancreatic α-amylase activity in non-pregnant ewes [93]. Similarly, dietary rumen-protected Arg supplementation to ewes during mid-to late-gestation did not influence pancreatic α-amylase activity of lamb offspring at 54 d of age [109].…”
Section: Influence Of Dietary or Luminal Nitrogenous Compounds On Pan...mentioning
confidence: 80%
“…More recent studies have evaluated the effects of dietary intake restriction on pancreatic α-amylase activity in ruminants. Dietary intake restriction decreased pancreatic α-amylase activity in nonpregnant ewes [93], pregnant ewes [94,95], and pregnant beef cows [96,97]. Changes in pancreatic α-amylase activity in response to changes in dry matter or energy intake may be related to the abundance and activity of pancreatic proteins involved in energy metabolism.…”
Section: Influence Of Dry Matter and Energy Intake On Pancreatic α-Am...mentioning
confidence: 98%
“…Increasing dietary levels of arginine results in increased hepatopancreatic α-amylase and trypsin activities in the Jian carp (Chen et al, 2012). Arginine administration through jugular infusion had no influence on pancreatic αamylase activity in nonpregnant ewes (Keomanivong et al, 2017b). However, it is unclear if maternal arginine supplementation could potentially influence offspring digestive enzyme activity in the pancreas or small intestine of ruminants.…”
Section: Introductionmentioning
confidence: 99%